Advancing shared decision making for symptom monitoring in people living beyond cancer. Issue 10 (October 2018) - Heathcote, Lauren C; Goldberg, Daniel S; Eccleston, Christopher; Spunt, Sheri L; Simons, Laura E; Sharpe, Louise; Earp, Brian D
Summary: Wellbeing after successful cancer treatment depends on more than merely reducing the risk of disease recurrence. Cancer survival can be characterised by uncertainty, fear, and the interpretation of bodily sensations as potentially symptomatic of cancer recurrence. This fear can lead to over-vigilance about bodily sensations and precautionary visits to the doctor, both of which can increase the chance of early detection but can also increase anxiety and decrease quality of life. In this Personal View, we consider the medical, psychological, and ethical issues related to the practice of self-directed symptom monitoring after completion of cancer treatment, focusing on the role of doctor–patient communication. We ask how clinicians can account for the plurality of values that patients might have when it comes to deciding on how to manage and respond to experiences of post-cancer symptoms. We advocate a shared decision-making approach that incorporates the assessment of an individual's cancer recurrence risks as well as psychosocial considerations regarding fear of cancer recurrence and mental health. We aim to raise awareness of the potential quality-of-life implications of symptom-monitoring practices, emphasising the need for a balance between physical and psychological health in people living beyond cancer.